Exercise training reduces inflammatory metabolic activity of visceral fat assessed by 18 F‐FDG PET/CT in obese women - Pahk, Kisoo; Kim, Eung Ju; Joung, Chanmin; Seo, Hong Seog; Kim, Sungeun (Clinical endocrinology (Oxford), 2020)
Obesity plays pivotal roles in the increased risk of cardiometabolic disease via induction of the inflammatory reaction from macrophages in visceral adipose tissue (VAT), which may elevate the inflammatory activity of VAT. This prospective study aimed to evaluate whether the inflammatory activity of VAT existed in association with systemic inflammation, and whether exercise could ameliorate the inflammatory activity of VAT assessed by F-fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) in obese women. A total of 23 obese women who participated in an exercise program were included. Subjects underwent F-FDG PET/CT before the start of the exercise program (baseline) and after the completion of the 3-month exercise program. For the assessment of VAT metabolic activity, the maximum standardized uptake value (SUVmax) and the mean standardized uptake value (SUVmean) were measured. The SUVmax of spleen, bone marrow (BM) and the high-sensitivity C-reactive protein (hsCRP) were used as a surrogate marker for systemic inflammation. Baseline SUVmax of VAT was positively correlated with the SUVmax of spleen, BM and hsCRP, whereas VAT SUVmean was not correlated. Exercise reduced SUVmax of VAT in addition to adiposity, the SUVmax of spleen, BM and hsCRP. However, VAT SUVmean was not significantly changed. Furthermore, the association of SUVmax of VAT, and the SUVmax of spleen, BM and hsCRP was no longer relevant after exercise. In obese women, the SUVmax of VAT assessed by F-FDG PET/CT was associated with systemic inflammation and exercise reduced the SUVmax of VAT and abrogated its association with systemic inflammation.